Participação cidadã de interface digital: entre o comunitário e o tecnocrático - Tavares, Luis Eduardo (2017)
The present work has as objective the critical reflection on the phenomenon of crossing between the practices of political participation of the citizens and the devices of digital communication. This interface manifests itself in a heterogeneity of forms that surround us today such as crowdsourcing, crowdfunding, civic hacking, open government experiences and public manifestations of connected multitudes that renew traditional practices of participatory citizenship. The work is qualitative and developed based on bibliographic review and case studies. What it shows is that these practices present themselves, on the one hand, as innovative and disruptive ways of extending the existing political institutions in order to deepen democracy and, on the other hand, as a modus operandi of a productive system whose purpose is before technical rather than ethical